Use of intraoperative ultrasound and surgical navigation in brainstem tumor resection: impact on accuracy, safety, and neurological outcomes-a systematic review - Amezcua, Karim Noe Zamora; Castro Cisneros, Isaac Andre; Cosme Rodríguez, Diego Fernando; Perea Gómez, Edinson Yair; García Cruz, Erick Antonio (International Journal of Research in Medical Sciences, 2025)
Brainstem tumors are among the most complex challenges in neurosurgery. They lie deep within the brain and sit close to critical nerves and blood vessels. Surgery in this region is risky and often difficult. To improve safety and precision, many neurosurgeons now use intraoperative ultrasound (iUS) and surgical navigation (SN). This review looks at how these tools affect the accuracy of tumor removal, safety during surgery, and patient outcomes. We followed PRISMA guidelines to search PubMed, Scopus, and Google Scholar. We included studies from 2020 to 2024 that focused on iUS or SN in brain tumor surgery. We selected studies that reported on the extent of resection (EOR), surgical safety, or neurological results. Data was collected independently using a standard format. Due to differences in study methods, we summarized results narratively. Nine studies met the criteria. They covered a range of patients and surgical settings. iUS showed a strong match with MRI for measuring tumor size (R2=0.97) and leftover tissue (R2=0.78). It improved EOR by 15-20% in several groups. In glioblastoma cases, 3D navigated iUS found residual tumor in 20% of patients during surgery. Pediatric studies showed near-total resection in 87% of cases, with very low risk of complications. SN reduced surgical errors, especially when used alongside iUS. Together, they improved navigation and surgical planning. iUS and SN help make brainstem tumor surgery safer and more precise. Using both tools together offers the best results. We need standard protocols and more surgeon training worldwide to expand their benefits.